Integration of Inflammation-Immune Factors to Build Prognostic Model Predictive of Prognosis and Minimal Residual Disease for Hepatocellular Carcinoma - Xu, Xin; Huang, Ao; Guo, De-Zhen; Wang, Yu-Peng; Zhang, Shi-Yu; Yan, Jia-Yan; Wang, Xin-Yu; Cao, Ya; Fan, Jia; Zhou, Jian; Fu, Xiu-Tao; Shi, Ying-Hong (Frontiers in Oncology, 2022)
Background: Tumor recurrence after hepatectomy is high for hepatocellular carcinoma (HCC) and minimal residual disease (MRD) could be the underlying mechanism. A predictive model for recurrence and presence of MRD is needed. Methods: Common inflammation-immune factors were reviewed and selected to construct novel models. The model consisting of preoperative aspartate aminotransferase, C-reactive protein, and lymphocyte count, named ACLR, was selected and evaluated for clinical significance. Results: Among the nine novel inflammation-immune models, ACLR showed the highest accuracy for overall survival (OS) and time to recurrence (TTR). At the optimal cut-off value of 80, patients with high ACLR (> 80) had larger tumor size, higher Edmondson’s grade, more vascular invasion, advanced tumor stage, and poorer survival than those with low ACLR (≤ 80) in training cohort (5-year OS: 43.3% vs 80.1%, P < 0.0001; 5-year TTR: 74.9% vs 45.3%, P < 0.0001). Multivariate Cox analysis identified ACLR as an independent risk factor for OS (HR = 2.22, P < 0.001) and TTR (HR = 2.36, P < 0.001). Such clinical significance and prognostic value were verified in validation cohort. ACLR outperformed extant models, showing the highest area under receiver operating characteristics curve for 1-, 3-, 5-year OS (0.737, 0.719, 0.708) and 1-, 3-, 5-year TTR (0.696, 0.650, 0.629). High ACLR correlated with early recurrence (P < 0.001) and extremely early recurrence (P < 0.001). In patients with high ACLR, wide resection margin might confer survival benefit by decreasing recurrence (median TTR, 25.5 vs 11.4 months; P = 0.037). Conclusions: The novel inflammation-immune model, ACLR, could effectively predict prognosis, and the presence of MRD before hepatectomy and might guide the decision on resection margin for HCC patients.